2010
DOI: 10.2217/imt.10.47
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in asthma

Abstract: Asthma is a chronic inflammatory disorder of the airways in which many cells and cellular elements play a role. Chronic inflammation is associated with airway hyper-responsiveness that leads to recurrent episodes of wheezing, breathlessness, chest tightness and coughing, as well as variable airflow obstruction within the lung. With time, such airflow obstruction may become permanent due to remodeling. It has been treated for more than 100 years by subcutaneous immunotherapy with allergen extracts but in recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 150 publications
(103 reference statements)
0
4
0
2
Order By: Relevance
“…Accumulating evidence have convincingly shown that in addition to alleviating symptoms, allergen specific immunotherapy can improve quality of life, reduce long-term costs and burden of allergies, and has the potential to change the course of the disease. Several appropriately designed and powered clinical trials have proven its good safety profile and effectiveness in allergic rhinitis, asthma and venom allergy [59,136,137]. …”
Section: Understanding the Allergy Epidemicmentioning
confidence: 99%
“…Accumulating evidence have convincingly shown that in addition to alleviating symptoms, allergen specific immunotherapy can improve quality of life, reduce long-term costs and burden of allergies, and has the potential to change the course of the disease. Several appropriately designed and powered clinical trials have proven its good safety profile and effectiveness in allergic rhinitis, asthma and venom allergy [59,136,137]. …”
Section: Understanding the Allergy Epidemicmentioning
confidence: 99%
“…The first improvement of ragweed AIT was the use of adjuvants (e.g., aluminum hydroxide, calcium phosphate, or tyrosine) and the chemical modification of extracts (allergoids), which lowered the risk of systemic side effects and enabled the faster achievement of the maintenance dose in comparison with aqueous extracts [98]. New adjuvants, such as monophosphoryl lipid A, the non-pyrogenic component of Salmonella minnesota LPS, combined with ragweed allergoid adsorbed to L-tyrosine, in order to boost its immunogenicity, are currently available [99, 100].…”
Section: Allergen-specific Immunotherapymentioning
confidence: 99%
“…Après stabilisation du patient, il sera possible de diminuer la corticothérapie inhalée par paliers de 25 à 50 % sur trois mois. D'autres thérapeutiques peuvent être utilisées : en premier lieu, la désensibilisation [13], qui a bénéficié de la voie sublinguale : elle peut être efficace dans les cas l'allergie aux acariens, spores de moisissures, ainsi qu'aux pollens et phanères d'animaux ; la kinésithérapie, l'exercice physique (natation) ; les traitements de terrain : thermalisme, homéopathie, acupuncture, oligo-éléments, phytothérapie ;…”
Section: Savoirsunclassified
“…des traitements nouveaux dans les asthmes sévères : antiIgE (omalizumab), anticorps monoclonaux anticytokines anti-IL4, anti-IL5, et anti-TNF [13].…”
Section: Savoirsunclassified